Augmented Reality in Early Childhood Education: Trends, Practices, and Insights from a Literature Review - Nirmala, Besse; Solihatin, Etin; Moch. Sukardjo, (International Journal of Interactive Mobile Technologies (iJIM), 2024)
In recent years, the use of augmented reality (AR) in early childhood education (ECE) has grown significantly. However, there remains a limited understanding of publication trends, research methodologies, and the overall impact of this technology. This study evaluates the evolution of AR in ECE from 2013 to 2023 through a comprehensive review of 49 articles published in journals indexed by Scopus. We employed VOS viewer for bibliometric analysis, alongside Google Scholar for database searches and Microsoft Excel for statistical evaluation. Three researchers conducted content analysis of the selected papers based on established criteria. Our findings reveal a consistent increase in AR-related publications in ECE over the past decade. In studies utilizing quantitative methods, participant numbers typically ranged from 30 to 100. Researchers developed AR applications using marker-based techniques and assessed their effectiveness through questionnaires. The results indicate that AR offers numerous advantages, including enhanced motivation, a supportive learning environment, improved academic performance, assistance for children with special needs, and promotion of social and emotional development. This study recommends that early childhood educators incorporate AR into their teaching practices as an innovative and engaging tool for future educational endeavors. This revision aims to improve readability while preserving the essential information and findings of your original abstract.